THE EFFECT OF CAPITAL STUCTURE ON THE COMPANY FINANCIAL PERFORMANCE IN THE COAL MINING SECTOR - Dewi Sarifah Tullah; Erma Apriyanti; Siti Nurjanah (Jurnal RAK (Riset Akuntansi Keuangan), 2022)
The aim of this study was to analyze the capital structure on financial performance. Capital structure is measured by the leverage ratio (solvability) through the total debt to total assets ratio (DAR), total debt to total equity ratio (DER), and long-term debt to equity ratio (LDER) proxies, while financial performance is measured by the profitability ratio using the Return on Asset (ROA) proxy. The study population is a coal mining company listed on the Indonesia Stock Exchange in 2014-2019. The purposive sampling method was chosen as a sampling method with certain criteria. The final sample size based on predetermined criteria was 96 (16 companies with an observation period of 6 years). Multiple linear regression was used to test the hypothesis. The results showed that DAR and LDER had a negative effect on ROA, while DER did not affect ROA.